The Role of Cognitive Conflict Approach to Improving Critical Thinking Skills and Conceptual Understanding in Mechanical Waves - Muh. Makhrus; Zul Hidayatullah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
This study aims to determine the effect of the cognitive conflict approach to critical thinking skills and conceptual understanding in mechanical wave material. This type of research is a Pre-experimental research design with One Group Pretest-Posttest Design. The study population was all students of class XI MIA MAN 2 Mataram with a sampling technique using purposive sampling. The research sample was students in all three classes that were used as experimental classes which were given treatment in the form of learning using the cognitive conflict approach. An instrument for critical thinking skills using student worksheet and description test. While the data of conceptual understanding was obtained by a multiple-choice test. Hypothesis testing in this research is a paired t-test and MANOVA test. The results of the hypothesis test give the conclusion that there is an effect of the cognitive conflict approach to critical thinking skills and conceptual understanding in mechanical wave students in MAN 2 Mataram in the three experimental classes.